Meta-Analysis of the Effectiveness and Safety of Intravenous Thrombolysis in Patients with Acute Cerebral Infarction. (7th December 2021) - Wu, Huili; Gong, Weiping; Tang, Yanyan; Xu, Wuhua; Zhou, Ying; Liu, Xianjun
Abstract : In this paper, a meta-analysis of the effectiveness and safety of intravenous thrombolysis in patients with acute cerebral infarction was carried out, the original literature inclusion criteria and retrieval strategies were developed, and the collection deadline was about new oral anticoagulants and other methods for the antithrombotic intravenous thrombolytic treatment of patients with acute cerebral infarction for the relevant literature on the safety and effectiveness comparison. First, the quality of the literature is evaluated according to whether the included studies are randomized controlled trials, whether there is randomized concealment, whether blinding is used, and whether they are withdrawn or lost to follow-up, and the RevMan 5.2 software is used for meta-analysis. At the same time, grey literature databases such as dissertations were experimentally searched, and all randomized controlled studies (RCT), nonrandomized controlled studies, case-controlled studies, cohort studies, case series reports, etc. of Wingspan in the treatment of intracranial atherosclerotic stenosis were collected. In the prevention of myocardial infarction in patients with acute cerebral infarction, the difference between the two was not statistically significant (RR = 0.82, 95% CI (0.57, 1.17), P = 0.27 ). Compared with other methods, it can significantly reduce the all-cause mortality of patients with nonvalvular venous thrombolysis, and the difference is statistically significant (RR = 0.90, 95% CI (0.85, 0.96), P = 0.001 ). Experimental results show that in terms of safety, the new oral anticoagulant is better than other methods in reducing minor bleeding in patients with acute cerebral infarction, and the difference is statistically significant (RR = 0.87, 95% CI (0.76, 0 99), P = 0.03 ); the effect is better than other methods in reducing the incidence of serious bleeding events, and the difference is statistically significant (RR = 0.79, 95% CI (0.74, 0.85), P < 0.00001 ).